Phosphate‐solubilising microorganisms for improved crop productivity: a critical assessment. Issue 3 (9th October 2020) - Raymond, Nelly S.; Gómez‐Muñoz, Beatriz; van der Bom, Frederik J. T.; Nybroe, Ole; Jensen, Lars S.; Müller‐Stöver, Dorette S.; Oberson, Astrid; Richardson, Alan E.
Summary: Phosphate‐solubilising microorganisms (PSM) are often reported to have positive effects on crop productivity through enhanced phosphorus (P) nutrition. Our aim was to evaluate the validity of this concept. Most studies that report 'positive effects' of PSM on plant growth have been conducted under controlled conditions, whereas field experiments more frequently fail to demonstrate a positive response. Many studies have indicated that the mechanisms seen in vitro do not translate into improved crop P nutrition in complex soil–plant systems. Furthermore, associated mechanisms are often not rigorously assessed. We suggest that PSM do not mobilise sufficient P to change the crops' nutritional environment under field conditions. The current concept, in which PSM solubilise P 'for the plant' should thus be revised. Although PSM have the capacity to solubilise P to meet their own needs, it is the turnover of the microbial biomass that subsequently provides P to plants over a longer time. Therefore, the existing concept of PSM function is unlikely to deliver a reliable strategy for increasing crop P nutrition. A further mechanistic understanding is needed to determine how P mobilisation by PSM as a component of the whole soil community can be manipulated to become more effective for plant P nutrition.